Kurangnya Etika dan Moral pada Anak Sekolah Dasar di Era Globalisasi - Ramadhan Putra Pamungkas; Diah Puri Widyawati; Tasya Putri; Dinda Zahra Ummami (Jurnal Manajemen Informatika & Teknologi, 2025)
The development of information technology in the era of globalization has a positive and negative impact on people's lives, including elementary school children. While technological advances open up unlimited access to science, the uncontrolled flow of information also affects children's moral values. This article discusses the problem of low ethics and morals in elementary school children, identifies the causative factors, explains the role of teachers as moral agents, presents guidance and counseling strategies, and provides practical recommendations for teachers. With the right strategy, teachers are expected to be able to help students face global moral challenges and grow as a generation of character.Keywords: Ethics, morals, elementary school children, globalization, counseling guidance, character education